Playing Past Racial Silence - Michael Domínguez; Alice Domínguez (Study and Scrutiny)
Too often, classroom conversations and literature choices frame race in homogenizing terms, equating racial identity solely with the experience of marginalization. This can have a chilling effect on students whose cultural context has made race an inaccessible topic, positioning conversations about racial identity beyond their zone of proximal development. Leveraging reflections from student-athletes and an analysis of three YA texts, the authors argue that sports-centered YA literature, by normalizing depictions of race, might be leveraged to serve as a critical entry point for robust classroom conversations about the complexity of racial identity, adding nuance and accessibility to a taboo subject.